Sirtuins mediate mitochondrial quality control mechanisms: a novel therapeutic target for osteoporosis - Zhang, Tianchi; Wang, Lining; Duan, Xiping; Niu, Yuanyuan; Li, Muzhe; Yun, Li; Sun, Haitao; Ma, Yong; Guo, Yang (Frontiers in Endocrinology, 2024)
Mitochondria plays a role in cell differentiation and apoptosis processes. Maintaining mitochondrial function is critical, and this involves various aspects of mitochondrial quality control such as protein homeostasis, biogenesis, dynamics, and mitophagy. Osteoporosis, a metabolic bone disorder, primarily arises from two factors: the dysregulation between lipogenic and osteogenic differentiation of aging bone marrow mesenchymal stem cells, and the imbalance between osteoblast-mediated bone formation and osteoclast-mediated bone resorption. Mitochondrial quality control has the potential to mitigate or even reverse the effects. Among the Sirtuin family, consisting of seven Sirtuins (SIRT1-7), SIRT1-SIRT6 play a crucial role in maintaining mitochondrial quality control. Additionally, SIRT1, SIRT3, SIRT6, and SIRT7 are directly involved in normal bone development and homeostasis by modulating bone cells. However, the precise mechanism by which these Sirtuins exert their effects remains unclear. This article reviews the impact of various aspects of mitochondrial quality control on osteoporosis, focusing on how SIRT1, SIRT3, and SIRT6 can improve osteoporosis by regulating mitochondrial protein homeostasis, biogenesis, and mitophagy. Furthermore, we provide an overview of the current state of clinical and preclinical drugs that can activate Sirtuins to improve osteoporosis. Specific Sirtuin-activating compounds are effective, but 2 further studies are needed. The findings of this study may offer valuable insights for future research on osteoporosis and the development of clinical prevention and therapeutic target strategies.